ANALISIS KEBEBASAN BERPENDAPAT TERHADAP AGAMA MENURUT PASAL 156A KUHP (STUDI KASUS PUTUSAN NOMOR 784/PID/2018/PT.MDN) - Livianto Sanjaya; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
Meliana was charged with violating Article 156a of the Indonesian Criminal Code and was sentenced by a Medan District Court judge with 18 months in prison for being considered a religious blasphemy for complaining about the volume of the call to prayer near her home. The problem is how freedom of expression relates to religion according to Article 156a of the Criminal Code. The research method used in writing this thesis is normative legal research. The results showed that the Medan District Court Judge considered that the element of